Graphene oxide: A stable carbon framework for functionalization - Eigler, Siegfried; Grimm, Stefan; Hof, Ferdinand; Hirsch, Andreas (Journal of Materials Chemistry A, 2013)
The effect of NaOH and HCl on the stability of the carbon framework in graphene oxide (GO) after substitution or etherification reaction in GO is demonstrated at 10 °C and 40 °C, respectively. Our results allow the preparation of functionalized GO based architectures with an intact σ-framework of carbon atoms. © 2013 The Royal Society of Chemistry.

Graphene oxide: Efficiency of reducing agents - Eigler, Siegfried; Grimm, Stefan; Enzelberger-Heim, Michael; Müller, Paul; Hirsch, Andreas (Chemical Communications, 2013)
The efficiency of reducing agents for the reduction of graphene oxide (GO) could be probed by scanning Raman spectroscopy. A film of graphene flakes derived from GO was probed to be graphene like. We also focus on the surface quality of reduced GO (rGO). © 2013 The Royal Society of Chemistry.

Investigation of the thermal stability of the carbon framework of graphene oxide - Eigler, Siegfried; Grimm, Stefan; Hirsch, Andreas (Chemistry - A European Journal, 2014)
In this study, we use our recently prepared graphene oxide (GO) with an almost intact σ-framework of carbon atoms (ai-GO) to probe the thermal stability of the carbon framework for the first time. Ai-GO exhibits few defects because CO formation is prevented during synthesis. Ai-GO was thermally treated before chemical reduction and the resulting defect density in graphene was subsequently determined by statistical Raman microscopy. Surprisingly, the carbon framework of ai-GO is stable in thin films up to 100°C. Furthermore, we find evidence for an increase in the quality of ai-GO upon annealing at 50°C before reduction. The carbon framework of GO prepared according to the popular Hummers' method (GO-c) appears to be less stable and decomposition starts at 50°C, which is qualitatively indicated by CO-trapping experiments in μm-thin films. Information about the stability of GO is important for storing, processing, and using GO in many applications. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Mapping Charge-Carrier Density across the p-n Junction in Ambipolar Carbon-Nanotube Networks by Raman Microscopy - Grimm, Stefan; Jakubka, Florian; Schießl, Stefan; Gannott, Florentina; Zaumseil, Jana (Advanced Materials, 2014)
In situ confocal Raman microscopy is used to map the recombination zone (induced p-n junction) in an ambipolar carbon-nanotube-network transistor with high spatial resolution. The shift of the 2D mode (G' mode) depending on hole and electron accumulation serves as a measure for the local charge-carrier density and provides complementary information about charge transport and recombination in ambipolar transistors.
EAM Import::2019-03-12

Statistical raman microscopy and atomic force microscopy on heterogeneous graphene obtained after reduction of graphene oxide - Eigler, Siegfried; Hof, Ferdinand; Enzelberger-Heim, Michael; Grimm, Stefan; Müller, Paul; Hirsch, Andreas (Journal of Physical Chemistry C, 2014)
Graphene oxide can be used as a precursor to graphene, but the quality of graphene flakes is highly heterogeneous. Scanning Raman microscopy (SRM) is used to characterize films of graphene derived from flakes of graphene oxide with an almost intact carbon framework (ai-GO). The defect density of these flakes is visualized in detail by analyzing the intensity and full width at half-maximum of the most pronounced Raman peaks. In addition, we superimpose the SRM results with AFM images and correlate the spectroscopic results with the morphology. Furthermore, we use the SRM technique to display the amount of defects in a film of graphene. Thus, an area of 250 × 250 μm of graphene is probed with a step-size increment of 1 μm. We are able to visualize the position of graphene flakes, edges and the substrate. Finally, we alter parameters of measurement to analyze the quality of graphene in a fast and reliable way. The described method can be used to probe and visualize the quality of graphene films. © 2014 American Chemical Society.

Trion Electroluminescence from Semiconducting Carbon Nanotubes - Jakubka, Florian; Grimm, Stefan; Zakharko, Yuriy; Gannott, Florentina; Zaumseil, Jana (ACS nano, 2014)
Near-infrared emission from semiconducting single-walled carbon nanotubes (SWNTs) usually results from radiative relaxation of excitons. By binding an additional electron or hole through chemical or electrochemical doping, charged three-body excitons, so-called trions, are created that emit light at lower energies. The energy difference is large enough to observe weak trion photoluminescence from doped SWNTs even at room temperature. Here, we demonstrate strong trion electroluminescence from electrolyte-gated, light-emitting SWNT transistors with three different polymer-sorted carbon nanotube species, namely, (6,5), (7,5) and (10,5). The red-shifted trion emission is equal to or even stronger than the exciton emission, which is attributed to the high charge carrier density in the transistor channel. The possibility of trions as a radiative relaxation pathway for triplets and dark excitons that are formed in large numbers by electron-hole recombination is discussed. The ratio of trion to exciton emission can be tuned by the applied voltages, enabling voltage-controlled near-infrared light sources with narrow line widths that are solution-processable and operate at low voltages (<3 V).
EAM Import::2019-03-13

Wet Chemical Synthesis of Graphene - Eigler, Siegfried; Enzelberger-Heim, Michael; Grimm, Stefan; Hofmann, Philipp; Kroener, Wolfgang; Geworski, Andreas; Dotzer, Christoph; Röckert, Michael; Xiao, Jie; Papp, Christian; Lytken, Ole; Steinrück, Hans-Peter; et al. (Advanced Materials, 2013)
A suitable technology for the preparation of graphene based on versatile wet chemistry is presented for the first time. The protocol allows the wet chemical synthesis of graphene from a new form of graphene oxide that consists of an intact hexagonal extgreeks-framework of C-atoms. Thus, it can be easily reduced to graphene that is no longer dominated by defects.